Upstream Sequences Involved in Regulating the Candida tropicalis Gene Encoding Peroxisomal Trifunctional Enzyme - Sloots, James (My University, 1993)
We have inestigated the expression of the genes hydratase-dehydrogenase-epimerase (HDE), acyl-CoA oxidase (AOX) and catalase (CATL) of the diploid yeast Candida tropicalis. These genes encode enzymes which are localized to the peroxisome. Expression of each gene was monitored by immunoblot analysis of yeast lysates using antibodies directed against each protein. We demonstrate that carbon sources influence expression of these genes, and do so in a coordinate fashion. We expressed C. tropicalis HDE in Saccharomyces cerevisiae and demonstrate that this trifunctional enzyme can be regulated by S. cerevisiae in a fashion that closely resembles that of C. tropicalis. Expression of constructs containing deletions in the upstream region of the HDE gene allowed us to localize regions responsible for regulating the expression of this gene. Regions were identified that are responsible for both repression by glucose and induction by oleic acid. A glucoseresponsive region lies between nucleotides -466 and -334. An oleic acid-responsive region lies between nucleotides -333 and -281. An additional region controlling derepression by nonfermentable carbon sources is located downstream of nucleotide -281. Comparison of the upstream nucleotide sequences of HDE, AOX and CATL both to each other, and to upstream regions of other oleic acid-responsive genes of C. tropicalis has identified possible consensus nucleotide sequences for glucose-and oleic acid-responsive upstream elements. Since the regulation of the HDE gene in S. cerevisiae closely resembles that of C. tropicalis, this implies that similar mechanisms of transcriptional control operate in both yeasts.
Regulation of Hydratase-Dehydrogenase-Epimerase
Keywords: candida tropicalis; gene; peroxisome; yeast; enzyme